Level of physical activity and barriers to exercise in adults with type 2 diabetes - Carolina Gómez Martin; Maria Laura Pomares; Carolina Maria Muratore; Pablo Javier Avila; Susana Beatriz Apoloni; Martín Rodríguez; Claudio Daniel Gonzalez (AIMS Press, 2021)
Introduction: Physical activity (PA) is an important element in type 2 diabetes mellitus (T2DM) management. The aims of this study were to assess the percentage of adults with T2DM who perform PA, according to the intensity level and to describe barriers to exercise and the association between metabolic control and other clinical variables. Methods: Multicenter, observational, cross-sectional study. Data were collected through the International PA Questionnaire (IPAQ) and the PA Barrier Questionnaire. Adults (18-65 years old) with T2DM from 17 Argentine diabetes centers were included, from May to July 2018. Results: A total of 270 men (54.9 ± 9.8 years) and 225 women (55.3 ± 9.6 years) were included. Duration of diabetes: 8.2 ± 6.3 years. The BMI in men was 32 ± 10.6 kg/m2, whereas that in women was 32.5 ± 7.2 kg/m2. The last two HbA1c values were 7.6 ± 1.7% and 7.5 ± 1.6. Results also showed that 12.7% had clinical heart disease, 13.7% had nephropathy, 20.8% had neuropathy, 6.1% had diabetic foot and 14.1% had retinopathy. The level of PA was low in 52.3% of the patients studied and moderate in 30.5%. The most frequent barriers were: "lack of will" (59.6%) and "lack of energy" (37.2%). The low level of PA was associated with age (OR: 1.05 per year of age; p < 0.001), HbA1c (OR: 1.16 per 1%; p < 0.05), BMI (OR: 1.06 per kg/m2; p < 0.001) and sex (OR: 1.69 for women; p < 0.01). Conclusions: PA in a cornerstone in management T2DM. Nevertheless, in this study, 52.3% of T2DM adults showed low level of PA. The main barriers reported were related to low personal motivation. These factors should be taken into account to implement programs to promote physical activity.